Postać Karola X Gustawa w świetle pamiętników Hugesa de Terlona, ambasadora Ludwika XIV przy królu Szwecji w latach 1656-1660 - Lik, Krzysztof (Acta Universitatis Lodziensis. Folia Historica, 2008)
Charles X Gustav is probably one of the most intriguing characters of the 17th century. Even his contemporaries could not establish any unambiguous opinions about him. The rumours about his achievements were often preceding the appearance of his person, not always arising favorable connotations. Apart from being considered an outstanding commander, tactician and politician, he quite fast obtained the reputation of „the brigand of Europe”, who was capable of beginning horrors of war in any part of the old continent. The limes of the Second North War and the person of Charles X Gustav have been always of great interest, even nowadays, in Scandinavian countries and became a constant element of their historical consciousness. This matter looks a little bit different on the other side of the Baltic Sea. Despite a huge interest in this period among Polish historians and numerous works written on this subject, our historiography did not devote much attention to the king of Sweden. What is more, he did not even have his own monograph, in the precise meaning of this word. One of the most valuable sources referring to Charles X Gustav are Memories of the ambassador of Louis XIV attached to the king of Sweden - Charles X Gustav in the years 1656-1660. Due to his position, the French diplomat - Huges dc Terlon, dedicated a lot of attention to the king of Sweden in his diaries. The image of the sovereign showed on the pages of his memories is undoubtedly very subjective, yet extremely valuable, taking into account the intimacy of the French ambassador with Charles X Gustav. What is more, this image is quite in - depth, as the memoirs’ author accompanied Charles X Gustav personally not only in Poland, but also in Denmark and Sweden, having a chance to observe the king in everyday situations, in different places as well as on different occasions. Charles X Gustav appears in the memoirs all the time. Even if there is no information referring to the king of Sweden directly, he turns up as spiritus movens of his diplomats, commanders or allies. As it is shown in the above reflections, Memories of the ambassador of Louis XIV by the king of Sweden - Charles X Gustav in years 1656-1660 seem to be a very interesting material. This preliminary research on the picture of the Swedish king may be an exciting contribution to a discussion about the image of Charles X Gustav in the Polish and European history.